Enhanced gas sensing in pristine carbon nanotubes under continuous ultraviolet light illumination - Chen, Gugang; Paronyan, Tereza M.; Pigos, Elena M.; Harutyunyan, Avetik R. (Scientific reports, 2012)
The advance of nanomaterials has opened new opportunities to develop ever more sensitive sensors owing to their high surface-to-volume ratio. However, it is challenging to achieve intrinsic sensitivities of nanomaterials for ultra-low level detections due to their vulnerability against contaminations. Here we show that despite considerable achievements in the last decade, continuous in situ cleaning of carbon nanotubes with ultraviolet light during gas sensing can still dramatically enhance their performance. For instance in nitric oxide detection, while sensitivity in air is improved two orders of magnitude, under controlled environment it reaches a detection limit of 590 parts-per-quadrillion (ppq) at room temperature. Furthermore, aiming for practical applications we illustrate how to address gas selectivity by introducing a gate bias. The concept of continuous in situ cleaning not only reveals the tremendous sensing potential of pristine carbon nanotubes but also more importantly it can be applied to other nanostructures.